Medication errors associated with carbapenems - A. V. Kuz'mina; I. L. Asetskaya; V. A. Polivanov; S. K. Zyryanov (Izdatelstvo OKI, 2018)
Purpose. The purpose of this study was to discover the prevalence and types of medication errors associated with the use of carbapenems. Materials and methods. We analyzed 161 spontaneous reports concerning adverse drug reactions associated with the carbapenems. All the reports were submitted to the Russian pharmacovigilance database between 01.01.2012 and 01.08.2014. Approved prescribing drug information, standards of medical care and practical guidelines for certain conditions were used to identify medication errors associated with specific products. Results. The prevalence of medication errors associated with the use of carbapenems was 24,8%. The reporters indicated medication error-related term only in 5,0% of these cases. The most common types of identified medication errors (44,0%) were deviations from the recommended dosing scheme, in most cases (20,0%) medication errors resulted from wrong frequency of administration of the antibiotic. Conclusions. The results of this study show that the reporters rarely recognize and identify medication errors. We suggest emphasizing the importance of compliance with the dosage regimen of antibiotics; the frequency of administration of carbapenems is critical.